EXPLORING FAMILY INVOLVEMENT OF PRE SCHOOL LEARNERS IN RAWALPINDI CITY - Saqiba Nawaz, Muhammad Arshad Dahar (JECCE, 2023)
The goal of this study was to learn more about preschool students' family participation in the city of Rawalpindi. This study used a descriptive co-relational research method to examine the impact of preschool students' family involvement on their academic achievement. In the city of Rawalpindi, the research focused on preschoolers and their parents. The study used random sampling methods. Data was gathered using a self-created questionnaire. The researcher personally visits representative schools to gather data. To evaluate the study instruments' reliability and validity, a pilot test was conducted. A sample of 30 parents was used to assess the survey's validity. Many responders took positive action to improve their kids' performance. Children in preschool who had initiative-taking parents did better. Most of the respondents said they occasionally talk to their preschoolers about how their academics are going. The study suggests that parents be made aware of the value of early childhood education so that they can comprehend their part in the academic success of their children